On the hidden transient interphase in metal anodes: Dynamic precipitation controls electrochemical interfaces in batteries - Stephen T. Fuller; J.-X. Kent Zheng (Proceedings of the National Academy of Sciences, 2025)
The solid–electrolyte interphase (SEI) formed on a battery electrode has been a central area of research for decades. This structurally complex layer profoundly impacts the electrochemical deposition morphology and stability of metal anodes. Departing from conventional approaches, we investigate metal dissolution—the reverse reaction of deposition—in battery environments using a state-of-the-art electroanalytical system combining a rotating-disk electrode and operando visualization. Our key finding is the presence of a transient SEI (T-SEI) that forms during fast discharging at high dissolution rates. We attribute T-SEI formation to local supersaturation and resultant electrolyte salt deposition. The T-SEI fundamentally alters the dissolution kinetics at the electrochemical interface, yielding a flat, clean surface. Unlike a classical SEI formed due to electrolyte decomposition, the T-SEI is “relaxable” upon removal of the enforced dissolution current; that is, the T-SEI dissolves back into the electrolyte when rested. The formation of T-SEI plays an unexpected critical role in the subsequent electrodeposition. When the metal is redeposited on a fully relaxed T-SEI surface, the morphology is remarkably different from that deposited on pristine or low-rate-discharged metal electrodes. Electron backscatter diffraction analysis suggests that the deposition occurs via growth of the original grains; this is in stark contrast to the isolated, new nuclei seen on standard metal electrodes without T-SEI formation. Using 3D profilometry, we observe a 42% reduction in surface roughness due to T-SEI formation. Our findings provide important insights into the kinetics at ion-producing electrochemical interfaces, and suggest a new dimension for engineering next generation batteries.